Burden of Alcohol Disorders on Emergency Department Attendances and Hospital Admissions in England. (28th June 2019) - Phillips, Thomas; Coulton, Simon; Drummond, Colin
Abstract : We provide analysis from a national routine dataset that quantifies the disproportionate burden of alcohol disorders on ED workload. Our analysis identifies 13 specific presentations predictive of alcohol disorders in ED with excess burden on hospital admission, total bed days and overall costs related to chronic alcohol disorders. Abstract: Aims: This study aims to estimate the prevalence and burden of alcohol disorders on Emergency Department (ED) and hospital inpatients in England through the exploratory analysis of NHS data. Methods: ED attendances and admission data were linked using hospital episode statistics. Diagnoses were preserved at a patient level to identify individuals who had an alcohol attributable diagnosis. Four groups were identified; a) individuals with no alcohol disorder (NAD), b) acute alcohol disorder (AAD), c) chronic alcohol disorder (CAD) and d) those with any alcohol disorder (AD) (b) and c) combined). Associations between ED diagnosis and alcohol disorders were examined using logistic regression adjusted for hospital provider, age and sex. Non-parametric tests were employed examining ED and hospital service use. Cost differences by group was explored using a propensity scored match sample. Results: Of the 1.2million subjects 6.7% were identified as having one or more AD accounting for 11.7% of ED attendances, 9.2% of hospital admissions and 7.2% total bed days. Bootstrapped derived means identified that hospital service use varied significantly between AAD and CAD. Whilst AAD accounted for greater attendances than NAD (2.78; 95% CI 2.680–2.879) those with CAD accounted for even greater attendances (4.33; 95% CI. 4.136–4.515), admissions (2.56; 95% CI. 2.502–2.625) and total bed days (15.14; 95% CI. 14.716–15.559). Conclusions: AD place a disproportionate impact on hospital services with CAD exerting the greatest burden on hospital utilization. The complexity and burden of CAD suggests this group should be a priority for intervention.